Antimicrobial action of methanol extract of Chromolaena odorata-Linn is logistic and exerted by Inhibition of Dehydrogenase Enzymes - CS, Alisi; LA, Nwaogu; CO, Ibegbulem; CU, Ujowundu (Journal of Research in Biology, 2011)
Inhibition of total dehydrogenase enzyme activity in pathogenic gram positive and gram negative micro organisms exposed to methanol extract of Chromolaena odorata was used as an index for assessment of its antimicrobial activity. Assay of total dehydrogenase enzyme activity was done in the test organisms (Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli) using 2,3,5-triphenyltetrazolium chloride (TTC) as an artificial electron acceptor which was reduced to the red-coloured triphenyl-formazan. Response of the bacterial isolates varied with extract concentration. Dehydrogenase activity was progressively inhibited in a logistic dose-response fashion. The gram negative Escherichia coli responded more markedly than Pseudomonas aureginosa and gram positive Staphylococcus aureus. Inhibitory concentrations (IC50) of the methanol extract against Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa were 208.49 μg/ml, 1361.01 μg/ml, and 903.08 μg/ml respectively. Preliminary phytochemical screening of the extract gave positive reactions for alkaloids, flavonoids, tannins, 4-hydroxybenzoic acid, and glycosides. These phytochemicals may be responsible for the observed inhibition of total dehydrogenase enzyme activity that translates to antimicrobial action in these pathogenic organisms